Heading representations in primates are compressed by saccades. Issue 1 (December 2017) - Bremmer, Frank; Churan, Jan; Lappe, Markus
Abstract Perceptual illusions help to understand how sensory signals are decoded in the brain. Here we report that the opposite approach is also applicable, i.e., results from decoding neural activity from monkey extrastriate visual cortex correctly predict a hitherto unknown perceptual illusion in humans. We record neural activity from monkey medial superior temporal (MST) and ventral intraparietal (VIP) area during presentation of self-motion stimuli and concurrent reflexive eye movements. A heading-decoder performs veridically during slow eye movements. During fast eye movements (saccades), however, the decoder erroneously reports compression of heading toward straight ahead. Functional equivalents of macaque areas MST and VIP have been identified in humans, implying a perceptual correlate (illusion) of this perisaccadic decoding error. Indeed, a behavioral experiment in humans shows that perceived heading is perisaccadically compressed toward the direction of gaze. Response properties of primate areas MST and VIP are consistent with being the substrate of the newly described visual illusion. Macaque higher visual areas MST and VIP encode heading direction based on self-motion stimuli. Here the authors show that, while making saccades, the heading direction decoded from the neural responses is compressed toward straight-ahead, and independently demonstrate a perceptual illusion in humans based on this perisaccadic decoding error.